Correlation of Initial Soil Density and Maximum Soil Density Under Drying-Wetting Cycles and Their Soil Erodibility - Tia Evriana; Trihanyndio Rendy Satrya; Mahendra Andiek Maulana; Wahyu Supriyo Winurseto (Departemen Teknik Sipil, Institut Teknologi Sepuluh Nopember, 2024)
The Serang - Panimbang Toll Road plan area of Banten province in regional stratigraphy from the starting station to the end consists of sedimentary rock sediments of the Bojongmanik Formation in the form of sandstone intersections with clayey limestone inserts that have been precipitated by the products of Karang volcano consisting of breccia and lava. This volcanic material exhibits a coarse soil texture, high water absorption capacity, and susceptibility to erosion. Soil erosion levels can be determined by measuring soil erodibility. Erosion often occurs in Indonesia because Indonesia has a tropical climate which has two seasons, the rainy and dry seasons. This climatic pattern contributes to the soil vulnerability to erosion, impacting its density. Therefore, it is important to know the effect of drying-wetting cycle on erodibility along the slope of Serang-Panimbang Toll Road. Soil samples will be modeled under two density variations: initial density and maximum density. Drying-wetting tests will determine the physical, mechanical, suction, and erodibility properties of soil. The results showed that there was an increase in the degree of saturation of 8.31% for the initial density soil and 17.12% for the maximum density soil. Unconfined compressive strength of the soil with initial density and maximum density also decreased in consistency which decreased from very stiff and stiff to very soft. However, erodibility values for both density conditions remained constant at 0.19 despite the drying-wetting cycles and is classified as low.